THE ACQUISITION OF ENGLISH VOCABULARY BY KINDERGARTEN STUDENTS THROUGH CHILDREN SONGS - Andari, Ida Ayu Made Yuni; Wiguna, Ida Bagus Alit Arta (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
This research focuses on how the process of students in acquiring language. This study aims to find out kinds of vocabulary that the young learners acquire through children song and analyze how the internal and external factors influence the process of language acquisition. The data in this study were 10 students from Hooray School In collecting the data, observation method and questioners were used. Observation was conducted for three weeks and post-test is given to the students in the last meeting of each week. Questioners is given to the students’ parents to know information about factors influence the students in learning English. The result of this study showed that English children songs are effective media to be used in acquiring language for children. In this study, there are 2 songs introduced to the students. From the lyrics of those songs, they are able to acquire English vocabularies, such as shark, octopus, jellyfish, turtle, dolphin, seahore, swim, and sea. In acquiring languages, the students are influenced by some factors. The internal factors are age, experience and learning style. The external factors consist of motivation, instruction and access to foreign speakers. The students who are surrounded by an English speaking environment learn English vocabularies faster and easier than the other students who are not surrounded by an English speaking environment.